2012
DOI: 10.1177/1758998312471253
|View full text |Cite
|
Sign up to set email alerts
|

Experiencing occupations with chronic hand disability: narratives of hand-injured adults

Abstract: Introduction. Hand injuries commonly account for a fifth of all emergencies presenting to emergency departments of most hospitals in Europe. One-third of these injuries lead to chronic hand disability that entails economical, psychological, physical and social implications on the wellbeing of hand-injured adults with long-term consequences. However, knowledge about the impact of chronic hand disability on occupations in the long term is limited. Methods. The purpose of this narrative study was to understand ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…Occupational adaptation was described in a majority of the studies as a manner of coping, being resilient, and as a use of appropriate strategies in response to altered or changing life situations (Dale et al, 2002;Nayar & Stanley, 2015). Several authors framed occupational adaptation during the presence of adverse life events as: (a) a result of engagement in occupations necessary for healing (Ammann, Satink, & Andresen, 2012); (b) a manner of reestablishing life balance (Gruwsved, Söderback, & Fernholm, 1996); (c) a process of overcoming disabling influences on occupational functioning (Bontje, Kinebanian, Josephsson, & Tamura, 2004); (d) an iterative process of occupational accommodation and occupational assimilation as experienced in a sense of loss (Hoppes & Segal, 2010); and (e) a process of reclaiming roles and participating in alternate occupations (Gibbs, Boshoff, & Stanley, 2015). In a grounded theory study approach to understanding the experiences of immigrant women, Nayar and Stanley (2015) defined occupational adaptation as a strategy to proactively respond to altered situations and broaden one's occupational choices.…”
Section: Thematic Analysismentioning
confidence: 99%
“…Occupational adaptation was described in a majority of the studies as a manner of coping, being resilient, and as a use of appropriate strategies in response to altered or changing life situations (Dale et al, 2002;Nayar & Stanley, 2015). Several authors framed occupational adaptation during the presence of adverse life events as: (a) a result of engagement in occupations necessary for healing (Ammann, Satink, & Andresen, 2012); (b) a manner of reestablishing life balance (Gruwsved, Söderback, & Fernholm, 1996); (c) a process of overcoming disabling influences on occupational functioning (Bontje, Kinebanian, Josephsson, & Tamura, 2004); (d) an iterative process of occupational accommodation and occupational assimilation as experienced in a sense of loss (Hoppes & Segal, 2010); and (e) a process of reclaiming roles and participating in alternate occupations (Gibbs, Boshoff, & Stanley, 2015). In a grounded theory study approach to understanding the experiences of immigrant women, Nayar and Stanley (2015) defined occupational adaptation as a strategy to proactively respond to altered situations and broaden one's occupational choices.…”
Section: Thematic Analysismentioning
confidence: 99%
“…Sustaining a hand injury is frequently unforeseen, which complicates the work-related transition process, as the individual will typically have limited time to prepare and adjust to the hand injury. Ammann et al (2014) reported that hand injuries were responsible for occupational disruptions, changes in occupational patterns and occupational limitations, which requires adaptations and creates immense challenges in a person’s daily life 20. This is likely to include the successful work-related transition of the person with the hand injury.…”
Section: Introductionmentioning
confidence: 99%
“…Returning to work is arguably the most important rehabilitation outcome for working‐age persons with serious hand injury. Whether a hand injury occurs unexpectedly or develops over time, it can nevertheless significantly impact performance of everyday occupations (Ammann et al, 2012 ; Bates & Mason, 2014 ), including work (Ammann et al, 2012 ; Kingston et al, 2016 ; Pichora & Grant, 2010 ; Siotos et al, 2018 ). Macro‐environmental factors, such as labour legislation and the unemployment rate, strongly influence work opportunities (Cho et al, 2012 ) and impact on whether a person is able to return to work (RTW) after sustaining a serious hand injury (Siotos et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…The effects of a hand injury on physical and psychosocial components of function (Chan & Spencer, 2004 ) require a process of adaptation, which may last as long as a year (Ammann et al, 2012 ). The resulting disruption may prevent full participation in work on a temporary or even permanent basis.…”
Section: Introductionmentioning
confidence: 99%